Effectiveness of Family-Based Education to Improve Disaster Preparedness among Mount Merapi Residents - Sari, Ilma Widiya; Bahri, Ahmad Syamsul; Hana Rosiana Ulfah (International Journal of Public Health Excellence (IJPHE), 2022)
Disasters can occur at any time in any part of the world with impacts on individuals, families and communities resulting in threats to the quality of life. Preparedness is the activities and steps taken in advance to ensure an effective response to the impact of a disaster. It takes the community in increasing preparedness for disasters by providing family-based education about disaster preparedness. This study aims to determine the effectiveness of family-based education in improving disaster preparedness. This research is a pre-experimental study with a post-test and pre-test one group design. The population of this research is families who live in areas prone to volcanic disasters. Samples were taken as many as 37 families with simple random sampling technique. The independent variable is family-based education and the dependent variable is disaster preparedness. The research data were analyzed to determine the difference in disaster preparedness during the pre-test and post-test using a paired t-test. The difference in the mean value of disaster preparedness before and after the intervention was statistically significant. The p-value was smaller than alpha (0.00 < 0.05), it can be concluded that family-based education is effective to improve disaster preparedness. Family-based education can help and encourage families to explore their strengths so that they can improve disaster preparedness.